Guanylyl cyclase/natriuretic peptide receptor-A signaling antagonizes phosphoinositide hydrolysis, Ca2+ release, and activation of protein kinase C - Pandey, Kailash N. (Frontiers in Molecular Neuroscience, 2014)
Thus far, three related natriuretic peptides (NPs) and three distinct sub-types of cognate NP receptors have been identified and characterized based on the specific ligand binding affinities, guanylyl cyclase activity, and generation of intracellular cGMP. Atrial and brain natriuretic peptides (ANP and BNP) specifically bind and activate guanylyl cyclase/natriuretic peptide receptor-A (GC-A/NPRA), and C-type natriuretic peptide (CNP) shows specificity to activate guanylyl cyclase/natriuretic peptide receptor-B (GC-B/NPRB). All three NPs bind to natriuretic peptide receptor-C (NPRC), which is also known as clearance or silent receptor. The NPRA is considered the principal biologically active receptor of NP family; however, the molecular signaling mechanisms of NP receptors are not well understood. The activation of NPRA and NPRB produces the intracellular second messenger cGMP, which serves as the major signaling molecule of all three NPs. The activation of NPRB in response to CNP also produces the intracellular cGMP; however, at lower magnitude than that of NPRA, which is activated by ANP and BNP. In addition to enhanced accumulation of intracellular cGMP in response to all three NPs, the levels of cAMP, Ca2+ and inositol triphosphate (IP3) have also been reported to be altered in different cells and tissue types. Interestingly, ANP has been found to lower the concentrations of cAMP, Ca2+, and IP3; however, NPRC has been proposed to increase the levels of these metabolic signaling molecules. The mechanistic studies of decreased and/or increased levels of cAMP, Ca2+, and IP3 in response to NPs and their receptors have not yet been clearly established. This review focuses on the signaling mechanisms of ANP/NPRA and their biological effects involving an increased level of intracellular accumulation of cGMP and a decreased level of cAMP, Ca2+, and IP3 in different cells and tissue systems.